Maine’s BTOP Information Commons Project: The Building Block to Statewide Digital Literacy Efforts - McKenney, Janet (Maine Policy Review, 2013)
Although Maine is a rural state, it has had success in keeping pace with technological changes since the rise of the Internet 20 years ago. In this section, authors describe some of these successes and the challenges faced by both consumers and libraries in the new digital environment. Janet McKenney discusses the recent BTOP [Broadband Technology Opportunities Program] federal grant that has increased the number of computers, workstations, and videoconferencing units in Maine libraries and is providing training and online learning resources to unemployed, low-income and senior citizens, along with assistance to local librarians to increase their technology skills.
Keywords: Maine; libraries; technology; information literacy; Internet access